The impact of hysterectomy on women's sexuality (Research, Society and Development, 2022)
Objective: we had the following objective: to describe the case series referring to the patient in the postoperative period of hysterectomy, including history, diagnosis, therapeutic management, specific care, criticism and referential confrontations. Method: This is an integrative review. The inclusion criteria were articles that were available in Portuguese and English available in full, dated in the last ten years and that included the impact of hysterectomy on female sexuality. A total of 332 publications were found, in which the titles and abstracts were analyzed, as well as the proposed inclusion and exclusion criteria. Then, n= 102 publications were pre-selected to be read in full in order to critically analyze the results obtained. In this, n= 322 publications were excluded for not meeting the inclusion criteria of the study. After the analysis process, n= 10 publications were selected to compose the results and presentation of this integrative review. Results: the association of laparoscopy and the consequent use of the vaginal route showed several benefits compared to the abdominal route: lower incidence of postoperative complications, less use of analgesics, that is, less postoperative pain, reduced hospital stay and early return to usual activities, confirming the findings in the literature. Conclusion: abdominal and vaginal hysterectomy, when well indicated, contribute to improving women's quality of life. Technical procedures, such as the incision to be used, will depend on the patient's biotype and the disease. The risk of morbidity for the patient is low, despite the search for better and updated results from her indications and contraindications.